Exposure in the Quranic story, an artistic analytical study (Journal of the College of Basic Education, 2022)
Praise be to God for what He has bestowed, and thanks be to Him for what He has inspired, and praise for what He has given, from the generality of the blessings He initiated, and the completion of the blessings He bestowed, among the most prominent of which was the Noble Qur’an and the master of the Messengers, Muhammad 6.And since the Arabic language is the language of the Qur’an, and the title of the identity of the Arab person, the scholars of the Arabic language have striven to study it, clarify it, and clarify its subtleties, to serve the Holy Qur’an first, and secondly to serve all Muslims, especially among them non-Arabs who were melodious in speech, and for that they knocked on all the doors of the Arabic language. serve that noble purpose.